Association between allergic conditions and colorectal cancer risk/mortality: a meta-analysis of prospective studies - Wangqian Ma (Nature Portfolio, 2017)
Abstract We aimed to assess the association between allergic conditions and risk/mortality of colorectal cancer (CRC). A systematic literature search was conducted using Pubmed and Embase to identify relevant studies. Prospective studies assessing the association between allergic conditions and risk/mortality of CRC were included. Risk ratios (RRs) were pooled with either a fixed- or a random-effects model according to heterogeneity. A total of 515379 participants and 10345 CRC cases from 12 studies were included in the analysis of CRC risk, while four studies with 1484741 individuals and 30040 CRC deaths were included in the analysis of CRC mortality. The pooled RR for the association between allergic conditions and CRC risk was 0.88 (95% CI 0.83–0.92). The inverse association was observed both in colon cancer (pooled RR = 0.83, 95% CI 0.72–0.97) and rectal cancer (pooled RR = 0.83, 95% CI 0.74–0.93). Moreover, no gender difference was observed in the analysis of CRC risk (for males, pooled RR = 0.88, 95% CI 0.81–0.96; for females, pooled RR = 0.88, 95% CI 0.82–0.95). And allergic conditions were also found to be inversely associated with CRC mortality (pooled RR = 0.88, 95% CI 0.83–0.92). In conclusion, the current meta-analysis provides further evidence that allergic conditions were inversely associated with CRC risk and mortality.